Pengaruh Literasi Akuntansi, Tingkat Pendidikan, dan Umur Usaha Terhadap Penggunaan Informasi Akuntansi pada UMKM se-Kecamatan Ubud - Dian Novita Sari; Cokorda Gde Bayu Putra; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2023)
The existence of MSMEs as a supporting pillar of the economy which has an impact on reducing poverty and unemployment in Indonesia as a developing country. However, a process in managing MSME is not easy to reverse its very strategic role. One of the problems faced by MSMEs is related to financial management. In this case accounting has a fairly important role in making decisions that will have an impact on survival MSMEs. Given the importance of recording expenses and income in the business being run, for this reason, MSME actors need to understand the use of accounting information. In a business, if accounting information is not applied effectively, businesses that have prospects for success may experience bankruptcy due to inaccurate decision making. The development of MSMEs in Ubud District has developed quite rapidly, reaching 10,459 MSME actors. The purpose of this study was to determine the effect of accounting literacy, education level, and business age on the use of accounting information in MSMEs throughout Ubud District. The sample used in this study was 99 MSME actors. The analytical method used is multiple linear regression analysis. The results of this study found that accounting literacy, education level, and business age partially had a positive and significant effect on the use of accounting information in MSMEs throughout Ubud District.